Toxic cyanobacteria in water a guide to their public health consequences, monitoring and management - Chorus, Ingrid; Welker, Martin (CRC Press, Taylor & Francis Group, 2021)
"Protecting drinking, recreational, and other water from toxic cyanobacteria has a major impact on health. This new edition outlines water-related exposure pathways, supports hazard analysis and risk assessment, and outlines strategies for their control and the design and implementation of monitoring programmes"--